Multipurpose conversion of marine diesel engines when creating piston motor-compressor units - V. L. Yusha; G. I. Chernov; I. D. Obukhov; O. G. Bessonov; V. V. Denisenko; A. A. Goncharenko; V. B. Shipov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This paper present an assessment of the energy efficiency of various combinations of piston stages of an internal combustion engine, a compressor, and a Rankine engine as part of piston motor-compressor units based on modernized marine diesel engines. An eight-cylinder single-row diesel engine 8Ch23/30-1 is chosen as the object of research, the base of which is used as a single platform for creating powertechnology units for various purposes and power. The proposed variants for converting the original engine allow, with minimal costs for the development of design and manufacturing technology, to create gas engine compressor units with reduced fuel consumption and improved weight and size characteristics in comparison with the known mobile compressor stations driven by diesel internal combustion engines. In the paper, on the basis of the developed mathematical models of working processes, the possibility of joint operation of diesel cylinders with piston expanders of the Rankine cycle and one or more stages of a piston compressor is assessed. Various possible combinations of diesel cylinders, compressor cylinders and expander cylinders are considered, as well as the dependences of engine power and compressor performance depending on the number of compressor stages and the number of diesel power cylinders used.